2007
DOI: 10.1007/s10750-007-9171-5
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of large branchiopod cysts: potential movement by wind from potholes on the Colorado Plateau

Abstract: Wind is suspected to be a primary dispersal mechanism for large branchiopod cysts on the Colorado Plateau. We used a wind tunnel to investigate wind velocities capable of moving pothole sediment and cysts from intact and disturbed surfaces. Material moved in the wind tunnel was trapped in filters; cysts were separated from sediment and counted. Undisturbed sediment moved at velocities as low as 5.9 m s -1 (12.3 miles h -1 ). A single all-terrain vehicle (ATV) track increased the sediment mass collected 10-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…Fairy shrimp egg bank densities were quite variable but, with exception of the highly exposed unvegetated pools that sometimes only held a couple of hundred eggs, recorded densities fell within the range of 10 3 -10 5 eggs per m 2 , which is typical for freshwater zooplankton (Brendonck and De Meester 2003). Using an experimental vacuum cleaner, Graham and Wirth (2008) showed that large branchiopod eggs from dry potholes in Utah (USA) are more easily picked up by wind from disturbed than from undisturbed egg banks. In disturbing the protective crust, human activities therefore could adversely affect populations of temporary pool invertebrates including fairy shrimp, which for their survival are highly dependent on the buffering capacity of the dormant egg bank.…”
Section: Egg Bank Sizementioning
confidence: 98%
See 1 more Smart Citation
“…Fairy shrimp egg bank densities were quite variable but, with exception of the highly exposed unvegetated pools that sometimes only held a couple of hundred eggs, recorded densities fell within the range of 10 3 -10 5 eggs per m 2 , which is typical for freshwater zooplankton (Brendonck and De Meester 2003). Using an experimental vacuum cleaner, Graham and Wirth (2008) showed that large branchiopod eggs from dry potholes in Utah (USA) are more easily picked up by wind from disturbed than from undisturbed egg banks. In disturbing the protective crust, human activities therefore could adversely affect populations of temporary pool invertebrates including fairy shrimp, which for their survival are highly dependent on the buffering capacity of the dormant egg bank.…”
Section: Egg Bank Sizementioning
confidence: 98%
“…In disturbing the protective crust, human activities therefore could adversely affect populations of temporary pool invertebrates including fairy shrimp, which for their survival are highly dependent on the buffering capacity of the dormant egg bank. Many inselbergs, notably in Southern Africa and Australia, but also rock pools in other areas such as the potholes on the sandstone flats in Utah are popular tourist destinations; and in some cases, hiking trails and four by four tracks pass right through pool sites damaging the egg banks (Graham and Wirth 2008;Vanschoenwinkel personal observation). Conservation managers should therefore consider better regulating these activities.…”
Section: Egg Bank Sizementioning
confidence: 99%
“…The action of wind on temporary ponds can potentially disperse microorganisms or resting stages both from water during the wet phase (Sharma et al, 2007), and from soil during the dry phase (Graham & Wirth, 2008). Wind-mediated dispersal is known as anemochory.…”
Section: Dispersal By Physical Vectorsmentioning
confidence: 99%
“…According to these authors, biological vectors are the only effective dispersal agents during the wet phase in temporary ponds. Conversely, during the dry phase, wind causes erosion of soil by detaching particles from its surface and moving zooplankton resting stages even when it blows at low speed (Graham & Wirth, 2008).…”
Section: Dispersal By Physical Vectorsmentioning
confidence: 99%
See 1 more Smart Citation